Histochemical mapping of the duration of action of photobiomodulation on cytochrome c oxidase in the rat brain - Wade, Zachary; Barrett, Douglas W.; Davis, Roger E.; Nguyen, Adrian; Venkat, Sindhu; Gonzalez-Lima, F. (Frontiers in Neuroscience, 2023)
This is the first study mapping the duration of action of in vivo photobiomodulation (PBM) on cytochrome-c-oxidase (CCO). In cellular bioenergetics, CCO is the terminal rate-limiting enzyme in the mitochondrial electron transport chain, which catalyzes oxygen utilization for aerobic energy production. PBM using transcranial infrared laser stimulation (TILS) is a promising intervention for non-invasively modulating CCO in the brain. TILS of the human prefrontal cortex directly causes CCO photo-oxidation, which is associated with increased cerebral oxygenation and improved cognition. This experiment aimed to map the duration of action of in vivo PBM on CCO activity in discrete neuroanatomic locations within rat brains up to 4 weeks after a single TILS session (50 sec, 1064 nm CW, 250 mW/cm2). Control brains from rats treated with a sham session without TILS (laser off) were compared to brains from TILS-treated rats that were collected 1 day, 2 weeks, or 4 weeks post-TILS. Cryostat sections of the 36 collected brains were processed using quantitative enzyme histochemistry and digitally imaged. Densitometric readings of 28 regions of interest were recorded and converted to CCO activity units of oxygen utilization using calibration standards. Data analysis (ANCOVA) compared each laser-treated group to sham with whole-brain average as a covariate. The prefrontal infralimbic cortex showed the earliest significant increase in CCO activity between 1day post-TILS and sham groups, which continued elevated for 2-4 weeks post-TILS. Significant differences in CCO activity between 2-weeks and sham groups were also found in the lateral septum, accumbens core, CA3 of the hippocampus, and the molecular layer of the hippocampus. The medial amygdala showed a significant decrease in CCO activity between 4-weeks and sham. Further analyses showed significant inter-regional CCO activity correlations among the brain regions as the result of TILS, with the most pronounced changes at 4-weeks post-stimulation. The time course of changes in CCO activity and network connectivity suggested that TILS caused different neuroplasticity types of bioenergetic changes at different time scales, depending on brain region and its depth from the cortex. In conclusion, this controlled CCO histochemical study demonstrated a long-lasting duration of action of PBM in the rat brain.